Gantry crane derailment and collapse induced by wind load. (August 2016) - Frendo, Francesco
Abstract: The catastrophic derailment of a gantry crane is analysed in the paper. Under the action of a persistent and very strong wind, with gusts at about 110 km/h, the crane started moving and, after having travelled for about 60 m, derailed and collapsed. Fortunately, no injured operator resulted from the event. The crane was endowed with passive rail clamps, which had to be dimensioned with reference to a very strong, i.e. out-of-service, wind intensity, given in standards. The analysis of technical data of the crane and of the installed clamps brought to the conclusion that a trivial error was made in the determination of the out-of-service wind load, since no aerodynamic coefficient was taken into account in the evaluation of the wind thrust. Due to this, the clamps didn't respond to the current regulations and, actually, were not capable of keeping the crane standing for the strongest wind load, which may occur in the region of the plant installation. The analysis, based on crane geometry and wind recordings, shows that, actually, the clamps capacity was exceeded by the wind load at the moment of the accident. A plane analysis of the crane loading condition, based on a beam model, allowed to explain the way the crane collapsed, with the rotation about a vertical axis of one of the leg, and to estimate the loads exchanged between the crane bogies and the rail, that caused the rupture of several rail anchoring bolts. The accident was caused by a design error and this points out the necessity of accurate evaluations, with multiple and independent checks, in particular in case of large plants with significant risk for operators, as in this case, or for the environment. Highlights: The derailment and failure of a gantry crane is discussed in the paper. The failure was caused by wind load. A trivial design error caused a bad design of the passive (anti-hurricane) clamps. An in-plane beam model is used to explain the crane derailment. The beam model also allowed to evaluate the force exchanged between bogies and the rail.